2021
DOI: 10.1016/j.jamda.2021.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Signs, Symptoms, and Comorbidities Associated With Onset and Prognosis of COVID-19 in a Nursing Home

Abstract: Background: Effective halting of outbreaks in skilled nursing facilities (SNFs) depends on the earliest recognition of cases. We assessed confirmed COVID-19 cases at an SNF impacted by COVID-19 in the United States to identify early indications of COVID-19 infection. Methods: We performed retrospective reviews of electronic health records for residents with laboratoryconfirmed SARS-CoV-2 during February 28eMarch 16, 2020. Records were abstracted for comorbidities, signs and symptoms, and illness outcomes durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Although obesity is a well-known risk factor for developing severe COVID-19 in the general population, 14 studies in older people have shown conflicting results. 33,34 The lack of association in our study may be related to the well-known obesity paradox in very old people, 35 for whom body-mass-index is a poor indicator of body composition and body fat distribution. 36 It has also been hypothesized that malnutrition could be an important risk factor, 37,38 but we did not find an association between food intake and mortality after adjustment for other risk factors, as in a previous study.…”
Section: Discussionmentioning
confidence: 74%
“…Although obesity is a well-known risk factor for developing severe COVID-19 in the general population, 14 studies in older people have shown conflicting results. 33,34 The lack of association in our study may be related to the well-known obesity paradox in very old people, 35 for whom body-mass-index is a poor indicator of body composition and body fat distribution. 36 It has also been hypothesized that malnutrition could be an important risk factor, 37,38 but we did not find an association between food intake and mortality after adjustment for other risk factors, as in a previous study.…”
Section: Discussionmentioning
confidence: 74%
“…In total, 26 studies reported on the mortality outcome among CLD and non-CLD patients ( 8 , 10 12 , 15 , 19 , 20 , 22 , 24 26 , 29 , 30 , 33 , 35 , 38 , 39 , 41 , 44 51 ). The pooled OR was 2.35 (95% CI, 1.84–3.00; I 2 = 96.26%; 95% PI, 0.76–7.18) ( Figure 3 ), indicating that COVID-19 patients with CLD had 2.35 times higher odds of dying as patients without CLD.…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, 25 studies reported the severity of the CLD and the non-CLD groups (9,10,(19)(20)(21)23,24,(27)(28)(29)31,32,34,36,37,(40)(41)(42)(43)(44)46,(49)(50)(51)(52). The pooled OR was 2.44 (95% CI, 1.89-3.16; I 2 = 91.3%; 95% PI, 0.79-7.55) (Figure 2), indicating that the odds of developing severe disease among COVID-19 patients with CLD were 2.44 times higher than among those without CLD.…”
Section: Severitymentioning
confidence: 99%
“…In this field, a clear conceptual and practical definition of "close contacts" according to specific features of the NH environment is required and evaluating the effectiveness of the different compartmentalization strategies enacted is recommended. [40][41][42] To support the reshaped environment and mission, services have been reorganized and increased, but, probably due to the limited resources available, the increased ventilation and coordination between the environmental cleaning and disinfection was enacted only in a few NHs, despite their relevance. 21,25,27 Nurses have been invited to also increase the standards of care by undertaking more checks/monitoring of the residents', not only to measure their vital signs but also to detect early changes 22,41,42 by using news tools and their clinical judgement and their deeper knowledge of the personal and clinical history of each resident.…”
Section: Dovepressmentioning
confidence: 99%
“…[40][41][42] To support the reshaped environment and mission, services have been reorganized and increased, but, probably due to the limited resources available, the increased ventilation and coordination between the environmental cleaning and disinfection was enacted only in a few NHs, despite their relevance. 21,25,27 Nurses have been invited to also increase the standards of care by undertaking more checks/monitoring of the residents', not only to measure their vital signs but also to detect early changes 22,41,42 by using news tools and their clinical judgement and their deeper knowledge of the personal and clinical history of each resident. However, given the lack of nurses and the increased needs, ensuring higher standards of monitorization might have led to missed care in some fundamental needs (eg, help with eating and hygiene).…”
Section: Dovepressmentioning
confidence: 99%